2022
DOI: 10.1515/ijmr-2021-8519
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural and magnetic characterization of spherical high entropy alloy CoCuFeNi particles by hydrogen reduction assisted ultrasonic spray pyrolysis

Abstract: The present study focuses on the synthesis, structural and magnetic characterization of CoCuFeNi high entropy alloy particles. The hydrogen reduction assisted ultrasonic spray pyrolysis method was used to synthesize nanocrystalline quaternary CoCuFeNi particles in a single step. The effect of synthesis temperature on the structure, morphology and the size of particles was investigated. The syntheses were performed at 700 °C, 800 °C, and 900 °C with 0.1 M concentration of metal nitrate salts precursor solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
2
0
Order By: Relevance
“…Based on the Debye-Scherrer formula, the average crystallite size of all HEA powders after 15 h of milling is between 7 and 25 nm [58]. The average crystallite size determined for the present HEAs is close to that reported for other HEAs such as AlCuCrFeMnW x [59] and CoCuFeNi [60]. In addition, all alloys (Table 5) have lattice strains between 0.56 and 1.85%.…”
Section: Phase Evaluationsupporting
confidence: 74%
“…Based on the Debye-Scherrer formula, the average crystallite size of all HEA powders after 15 h of milling is between 7 and 25 nm [58]. The average crystallite size determined for the present HEAs is close to that reported for other HEAs such as AlCuCrFeMnW x [59] and CoCuFeNi [60]. In addition, all alloys (Table 5) have lattice strains between 0.56 and 1.85%.…”
Section: Phase Evaluationsupporting
confidence: 74%
“…This creates a strong incentive to innovate and fabricate electrocatalysts that are cost-effective, exceptionally efficient, and easily accessible, surpassing the catalytic performance of noble metals and conventional alloys, hence the importance of HEAs in catalytic applications such as the hydrogen evolution reaction (HER), oxygen reduction reaction (ORR), oxygen evolution reaction (OER), CO 2 reduction reaction (CO 2 RR), and ammonia (NH 3 ) decomposition [9]. In their study on the synthesis of Co CuFeNi particles by hydrogen reduction-assisted ultrasonic spray pyrolysis (USP-HR), Küçükelyas and his co-workers found that these particles exhibited high ferromagnetic behavior, making them promising materials for catalytic applications [10]. Also, silver (Ag) nanoparticles, due to their unique properties and high surface area, have often been used as catalysts in catalytic processes.…”
Section: Introductionmentioning
confidence: 99%
“…HEA refers to a solid solution composed of five or more elements, typically with atomic ratios ranging from 5% to 35%. , Note that the elemental ratios of HEA may deviate from this range. Alternatively, the definition of HEA can also be based on mixed entropy, where materials are considered to have HEA structures when the overall mixing entropy (Δ S mix ) is equal to or greater than 1.5 R , with R representing the molar gas constant (see the Supporting Information for details). , HEA exhibits distinct physiochemical properties due to the interactions among its multiple components, displaying four effects: thermodynamic high entropy, structural lattice distortion, kinetic sluggish diffusion, and “cocktail” effects. , Moreover, the tunable elemental compositions and abundant active sites of HEA nanostructures make them promising candidates for electrocatalytic water splitting and other energy-related applications with excellent activity and stability. However, traditional methods (e.g., arc melting, and vacuum induction melting , ) used to prepare HEA have predominantly resulted in large-sized bulk HEA materials with limited specific surface areas, thereby greatly hindering their electrocatalytic applications. , Notably, it is also challenging to accurately predict the kinetic mechanism and reaction pathway by first-principles calculations due to the complex composition and “cocktail” effect. Recently, to produce HEA nanoparticles with ultrafine particle size and controlled crystal phase, considerable efforts have been devoted to investigating ultrafast manufacturing strategies under extreme conditions, such as spray pyrolysis (SP), , microwave heating (MH), , laser ablation in liquid (LAL), laser engineered net shaping (LENS), , high-temperature shock (HTS), etc. However, it still remains a significant challenge to obtain ultrafine-sized HEA-NPs with diameters below 5 nm via ultrafast synthesis methods.…”
mentioning
confidence: 99%
“…13,40 Notably, it is also challenging to accurately predict the kinetic mechanism and reaction pathway by first-principles calculations due to the complex composition and "cocktail" effect. Recently, to produce HEA nanoparticles with ultrafine particle size and controlled crystal phase, considerable efforts have been devoted to investigating ultrafast manufacturing strategies under extreme conditions, such as spray pyrolysis (SP), 41,42 microwave heating (MH), 16,43−45 laser ablation in liquid (LAL), 46 laser engineered net shaping (LENS), 47,48 high-temperature shock (HTS), 49−52 etc. However, it still remains a significant challenge to obtain ultrafine-sized HEA-NPs with diameters below 5 nm via ultrafast synthesis methods.…”
mentioning
confidence: 99%